Pseudosperma umbonatum sp. nov. from Himalayan forests of Pakistan - Jabeen, Sana; Razzaq, Annum; Aqdas, Fauzia; Iqbal, Hira; Ijaz, Hira; Izhar, Aiman; Kamran, Muhammad; Naseer, Arooj; Khalid, Abdul Nasir (Phytotaxa, 2025)
A new species, Pseudosperma umbonatum was collected from different localities of Himalayan region of Khyber Pakhtunkhwa and Punjab in Pakistan. The species is characterized by its fibrillose pileus, ovoid to ellipsoid basidiospores (7.2–7.9 × 4.7–5.4 µm), and clavate to fusiform or ventricose septate cheilocystidia. Molecular phylogenetic analysis of DNA sequences from ITS and LSU regions supported it as a new species.